The elements for designing and developing the front office instructional module: Fuzzy Delphi technique - Sulaiman, Tajularipin; Quah, Wei Boon; Razali, Fazilah (SEAAIR Secretariat, 2024)
Incorporating experiential learning methods into classroom activities is crucial for creating an immersive on-campus experience. Front Office students require proficiency in communication, practical skills, knowledge application, and dispositional skills. This study aims to identify the essential elements necessary to integrate scenarios and resources for designing an online scenario-based learning module named the e-SBL FOIM-ATG for front-office courses in a Community College. The research design follows a quantitative approach, utilizing the Fuzzy Delphi technique. Research data was collected through a questionnaire administered to fifteen experts specializing in hospitality (Front Office), educational technology, scenario based learning, and curriculum development. Analysis of the data revealed that the experts reached a consensus on all elements, with consensus values exceeding 75%, threshold value (d) ≤ 0.2, and fuzzy score (A) ≥ α-cut value = 0.5. This consensus confirms the importance of these elements in developing the Front Office Instructional Module – Advise the Guest at the Community College. This research holds significant implications for lecturers, students, and the broader education system in Malaysia, promoting the adoption of scenario-based active learning as a transformative educational approach.